Development of an Evangelism-Based Missiology Course Curriculum - Oloria Malau; Sabar Rudi Sitompul; Septina Rumiris Sitorus; Sarah Sirait (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to produce teaching materials that follow the progress of the times. To produce teaching materials that suit the equipment needs of teachers as educators and evangelists. To increase the awareness of students who work as educators and evangelists. To determine the suitability of teaching materials to equip students to become evangelists and educators. The development research uses a questionnaire instrument with a Likert scale with five alternative answer choices. Data analysis was carried out using quantitative descriptive analysis techniques. This development research resulted in a new curriculum for the Missiology course in the PAK Study Program. Curriculum development refers to the 4 D model, namely the Define, Design, Development, and Disseminate Stage. However, this research shows a feasibility assessment only up to stage 3, namely the development stage. According to the Curriculum Expert, the result was 75%, so it was categorized as agreeing or feasible. The results of the curriculum feasibility assessment by the mission practitioner experts were